Bibliometric Analysis of Microlearning Research Results in the World of Education - Diana Susanti; Shakinaz Desa (Postgraduate, University of Mataram, 2026)
The rapid development of information and communication technology (ICT) has accelerated the adoption of microlearning in education; however, a comprehensive overview of its research trends remains limited. This study aims to examine the development of microlearning research in education over the past decade, with particular attention to publication growth, dominant subject areas, and leading contributing countries. A bibliometric approach was employed to analyze 201 documents indexed in the Scopus database, published between 2016 and 2025. Literature retrieval was conducted using the keywords “microlearning,” “micro-learning,” and “education.” Inclusion criteria covered English-language journal articles and conference proceedings focusing on microlearning applications in educational contexts, while unrelated documents and incomplete records were excluded. Data were analyzed using Bibliometrix (Biblioshiny) and VOSviewer to identify publication trends, subject area distribution, country contributions, and network structures through co-authorship, keyword co-occurrence, and citation analyses. The findings reveal a significant increase in publications, particularly between 2020 and 2025, with strong representation in social sciences, psychology, economics, and politics, surpassing computer science and information technology. The United States, Germany, and China emerged as the most influential contributors. Overall, microlearning demonstrates strong potential to enhance learning outcomes through flexible, concise, and technology-supported instructional approaches.